TRAckERS: Transfusion-Related Adverse Events Reporting System - Mohammad, Masrin; Toh, Shi Yin; Bong, Chih How; Hamdi, M. M.; Lee, Nung Kion (2018)
This study examine the efficiency and effectiveness of the procedure of reporting the transfusion-related adverse events. Blood transfusion is a process of receiving blood through an intravenous (IV) line from patient’s blood vessels. It is considered as a safe and common procedure as most of the blood transfusion goes well. However, there are still some minor or severe problems developed occasionally. These transfusion-related adverse events need to be investigated to find out the cause of adverse reaction during or after the blood transfusion. In Malaysia, although there is a procedure of reporting the adverse event that need to be follow strictly by the medical staff, there are some issues happens such as unattended cases, lack of detail, incomplete report and so on.